Do Maternal Depression and Self-Esteem Moderate and Mediate the Association Between Intimate Partner Violence After Childbirth and Postpartum Suicidal Ideation?. Issue 4 (1st October 2020) - Islam, Md. Jahirul; Broidy, Lisa; Mazerolle, Paul; Baird, Kathleen; Mazumder, Nurunnahar; Zobair, Khondker Mohammad
Abstract : Intimate partner violence (IPV) during the perinatal period is believed to have an adverse effect on maternal mental health. Given the risks of suicide and related public health concerns, the aim of this study is to examine (1) the association of experiencing physical, psychological, and sexual IPV after childbirth on postpartum suicidal ideation (SI), and (2) whether postpartum depression and self-esteem act to mediate or moderate the relationship between IPV and postpartum SI. A cross-sectional survey was conducted from October 2015 to January 2016 in the Chandpur District of Bangladesh among 426 new mothers, aged 15 to 49 years, who were in the first 6 months postpartum. Multivariate logistic regression models were used to examine the association between experiencing IPV and postpartum SI, controlling for a range of other known influences. The prevalence of postpartum SI was 30.8%. Accounting the influence of other confounders, the odds of postpartum SI were significantly higher among women who reported physical IPV victimization (adjusted odds ratio: 2.65; 95% confidence interval = 1.36, 5.18) at any point during the first 6 months following childbirth as opposed to those who did not. In addition, postpartum depression increased postpartum SI, while high self-esteem significantly reduced reports of SI. Both postpartum depression and maternal self-esteem notably mediate and moderate the effect of physical IPV after childbirth on postpartum SI. The findings illuminate that IPV victimization after childbirth significantly increases the odds of postpartum SI. This study reinforces the need to detect women with a history of IPV who may be at risk for SI, not only to offer them help and support but also to prevent or reduce SI.